Pengaruh pola makan terhadap kejadian stunting - Handayani, Trisna Yuni; Sari, Desi Pramita; Putri, Mona Rahayu (UKInstitute, 2024)
Stunting is a condition of the baby that fails to grow due to a chronic lack of nutrition resulting in an inconsistency between body height and age. Nutritional problems in infants will affect their ability to develop physically and cognitively to the maximum in the future. There are several factors that contribute to the occurrence of stunting. One contributing factor is the inadequate intake of nutrients observed in babies, characterized by an imbalance between the amount of food consumed and the recommended dietary requirements. Baby’s dietary habits have a significant impact on the consumption of essential nutrients that facilitate optimal growth and development. The research design selected for this study is cross-sectional. The sample was comprised of 96 participants. Sampling refers to the deliberate and intentional selection process in research, in which individuals or elements are selected based on specific criteria and objectives. The Food Frequency Questionnaire (FFQ) is a method used for anthropometric assessment. The Chi-Square test is used for data analysis. The findings of the study revealed a statistically significant p-value of 0,000, which indicates an important relationship between diet and the occurrence of stunting in babies. Nutritional intake is very important, as it relates not only to the dietary choices made by the individual, but also to the nutritional practices applied by the mother. The latter, the application of a diet, has been identified as a factor contributing to the occurrence of stunting. Effective work should be done in health care to ensure the provision of health education to mothers about the importance of food delivery patterns, quality, and diversity. It is very important to meet the nutritional needs of the baby.